Nrf2 activation as target to implement therapeutic treatments - Bocci, Velio; Valacchi, Giuseppe (Frontiers in Chemistry, 2015)
A chronic increase of oxidative stress is typical of serious pathologies such as myocardial infarction, stroke, chronic limb ischemia, chronic obstructive pulmonary disease (COPD), type II-diabetes, age-related macular degeneration leads to an epic increase of morbidity and mortality in all countries of the world. The initial inflammation followed by an excessive release of reactive oxygen species (ROS) implies a diffused cellular injury that needs to be corrected by an inducible expression of the innate detoxifying and antioxidant system. The transcription factor Nrf2, when properly activated, is able to restore a redox homeostasis and possibly improve human health.